Plasticidade morfológica em microalgas verdes do gênero Ankistrodesmus induzida por compostos liberados por Daphnia magna - Andolfato, Nathan Eugeni (2020)
Phenotypic plasticity in phytoplankton can be a defense mechanism against predation, directly affecting primary producers and consumers and the food chain of aquatic ecosystems. However, morphological plasticity as a defensive mechanism is an observed induced defense in only a few groups of microalgae. Some studies have documented that the defense induced in phytoplankton can be triggered merely by the presence of products released by herbivorous microcrustaceans, the kairomones, even in the absence of the predator. However, rare studies address predation-induced morphological plasticity in the cosmopolitan green microalgae of the family Selenastraceae. In this study, we evaluated the morphological variation (length and width) in 4 different species of 8 strains of microalgae of the genus Ankistrodesmus under the effect of kairomones by a cladoceran, Daphnia magna. The results showed that the presence of kairomones released by the predator induced an increase in the length and width of the cells of most strains of Ankistrodesmus. The width increased more sharply than the length, which may be related to the orientation of cell intake by the predator. As reported in another study for an A. falcatus strain, we found no colony maintenance or cell aggregation as an important morphological plasticity. However, the results suggest that a single strain of A. fusiformis (CCMA-UFSCar 605) produced colonies in the presence of kairomones excreted by the cladoceran. Despite the differences in time, intensity of response and type of induced change, all 8 strains (4 species) of the genus Ankistrodesmus studied showed some type of phenotypic plasticity in the presence of the predator's kairomones. This is the first report of changes in Ankistrodemus cell size under the influence of zooplankton predation (kairomones). The results are important to understand the ecology of these microalgae and highlight the importance of ecological studies for a better description of the taxonomic characteristics of the coccoid green microalgae.